Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jmv.27683
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of a high‐throughput screening assay for in vitro anti‐SARS‐CoV‐2 activity: Evaluation of 5676 Phase 1 Passed Structures

Abstract: Although vaccines are currently used to control the coronavirus disease 2019 (COVID‐19) pandemic, treatment options are urgently needed for those who cannot be vaccinated and for future outbreaks involving new severe acute respiratory syndrome coronavirus virus 2 (SARS‐CoV‐2) strains or coronaviruses not covered by current vaccines. Thus far, few existing antivirals are known to be effective against SARS‐CoV‐2 and clinically successful against COVID‐19. As part of an immediate response to the COVID‐19 pandemic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…3 ), making these cells more interesting for the selection of potential candidate drugs with promising therapeutic indices that can be further explored in follow-up in vivo studies. In addition, Vero E6 cells might be less suitable for the antiviral screening of small molecules due to their limited capacity to metabolize drugs compared to human-derived cells, as demonstrated for remdesivir in several reports ( Uemura et al, 2021 ; Chiu et al, 2022 ; Ramirez et al, 2021 ) and confirmed by our study ( Supplementary Fig. 3 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3 ), making these cells more interesting for the selection of potential candidate drugs with promising therapeutic indices that can be further explored in follow-up in vivo studies. In addition, Vero E6 cells might be less suitable for the antiviral screening of small molecules due to their limited capacity to metabolize drugs compared to human-derived cells, as demonstrated for remdesivir in several reports ( Uemura et al, 2021 ; Chiu et al, 2022 ; Ramirez et al, 2021 ) and confirmed by our study ( Supplementary Fig. 3 ).…”
Section: Discussionsupporting
confidence: 82%
“…Major efforts are ongoing to develop novel therapeutics for COVID-19 treatment and/or effective prophylactic approaches to prevent viral spread ( Yadav et al, 2021 ). In the context of early preclinical studies for SARS-CoV-2 antiviral assessment, screening platforms for drug libraries rely on the use of robust cellular infection systems, mostly based on immortalized cell lines originating from respiratory, but most often non-respiratory, tissues ( Murgolo et al, 2021 ; Uemura et al, 2021 ; Chiu et al, 2022 ; Ramirez et al, 2021 ; Grau-Exposito et al, 2022 ; Ko et al, 2021 ; Chu et al, 2020 ). In fact, many initial screenings for SARS-CoV-2 antivirals have largely utilized the African green monkey kidney cell line Vero E6 as the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of this system is that it relies on in situ detection of nsp5 proteolytic activity, which is highly specific to SARS-CoV(−2) infection, in contrast to other cell-based protocols relying on indirect and/or late impacts of infection, such as the measure of syncytia formation ( Buchrieser et al, 2020 ) or of cell mortality ( Riva et al, 2020 ; Belouzard et al, 2022 ; Chiu et al, 2022 ). Moreover, it allows for quantification of infection with any of the yet arisen variants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the classical low-throughput plaque reduction and RT-qPCR assays, potential high-throughput cell-based methods for SARS-CoV-2 antiviral screening include assays based on the use of recombinant infectious viruses or replicons expressing a luciferase and/or fluorescent protein ( Xie et al, 2020 ; Ricardo-Lax et al, 2021 ; Tanaka et al, 2022 ), which, however, are not easily adaptable to the multiple and quickly evolving SARS-CoV-2 variants. Other assays not restricted to a single variant are based on immunofluorescence staining using antibodies against specific SARS-CoV-2 proteins ( Bakowski et al, 2021 ) or on the assessment of the general cytopathic effect or of syncytia formation several days after inoculation ( Buchrieser et al, 2020 ; Riva et al, 2020 ; Belouzard et al, 2022 ; Chiu et al, 2022 ), but those approaches are often quite time-consuming and/or labor-intensive. In order to develop an easier-to-use assay, the aim of this study was to construct a fluorescent reporter cell line, allowing for a fast and automated read-out of the SARS-CoV-2 infection, and requiring minimal handlings to ensure maximum safety in a BSL-3 environment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent high-throughput screening (HTS), DOX was shown to have promising antiviral activity against SARS-CoV-2 in Caco-2 cells and HEK293 cells [ 29 ]. In another in silico study, doxorubicin was found to interact with the main protease and inhibit SARS-CoV-2 replication, but no study has been conducted on MERS-CoV [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%